Development of a virtual counseling room model to increase student interest in using guidance and counseling services - Dian Rezki Amelia Firdaus; Farida Aryani; Abdullah Pandang; Abdullah Sinring (Program Studi bimbingan Konseling PPs UNM Makassar, 2022)
The objectives of this study: (1) to describe the need for developing a virtual boarding school room model to attract students' interest in participating in counseling and guidance services, (2) to determine the prototype of a virtual boarding school room model and (3) to determine the validity and practicality of the virtual boarding school room model. This study uses the research and development method (Research & Development) developed by Borg and Gall. Data analysis used quantitative data analysis. The subjects in this study consisted of learning media experts, counseling guidance experts, BK practices and students who were taken using random sampling techniques. The results showed that (1) the development of a virtual counseling room model was needed by BK teachers and students, (2) a prototype virtual counseling room model was a media created using a google slide application that contained several counseling guidance services, (3) a room model Virtual counseling has the value of usability, service, and accuracy so that it is declared valid and practical to be used as media guidance and counseling.